Review: Antibacterial Behavior of Carboxylate Silver(I) Complexes - Paez-Collio, M; Paez-Collio, M; Azocar-Guzman, M; Azocar-Guzman, M; Levín-Vásquez, P; Levín-Vásquez, P (Taylor and Francis Ltd., 2014)
(Graph Presented) Since ancient times, silver ions have been known to be effective against a broad range of micro-organisms but in the last decade, this metal has been greatly studied because of their antimicrobial capability against a wide range of bacteria, viruses, and fungi. For the same reason, it is the most extensively studied metal with antibacterial applications in medicine. Besides applications, the antimicrobial activity is associated with high effectiveness, low toxicity, and virtually no resistance of micro-organisms to the presence of this metal. The appearance of new bacterial strains resistant to antibiotics is a serious health problem; so, there is a strong incentive to develop new bactericides. This makes current research in bactericidal silver complexes particularly important. This review summarizes the most important aspect related to coordination chemistry of Ag(I) carboxylate complexes and their influence as antibacterial agents. © 2014 Taylor & Francis.